Women’s Participation in Village Developent Planning: Case of Indonesia - Andryanto, Dian (FIA UB, 2021)
The introduction of participatory processes concerning village development planning by Law 6/2014 on Village open up the opportunity for village communities to shape village development priorities. It is expected that village community involvement over village planning will make village government more accoutable downwardly and village development be responsive to villagers problems and needs. Using literature review, the present paper inspects closely a body of literature to ensure that women and other historically marginalized groups have chance to participate meaningfully in these processes. The reviewed literature suggest a divergence between what scholars believe about advantages of participatory processes and limited impact of such. Similarly, within this nascent stage of village law implementation participatory spaces in determining village development priorities are still dominated by village elites and men, and village development is heavily focus on infrastructure development. However, the presence and empowered women’s organizations or groups which exists in villages might influential to drivw village development priorities that are responsive for women. What we learned from these body of literature is that meaningful participation by women and other historically disadvantaged groups can only be achieved through continious intervention and facilitation either by dedicated and reform-minded public officials and other critical actors. Furthermore women should involve in participatory village development planning as a collective, rather than as individuals.